Evaluasi Kualitas dan Kesuksesan Sistem Informasi Batu Among Tani Teknologi (BATT) dengan Menggunakan Pendekatan Technology Acceptance Model (TAM) dan Delone & Mclean - Arrofiq Budi Al Fajri; Admaja Dwi Herlambang; Satrio Hadi Wijoyo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Batu Among Tani Technology is an information system where there are three applications that are integrated into information system of BATT, the three applications are Among Tani, Among Kota, and Among Warga applications. The creating of BATT information system is purposed to prosper and serve the society of Batu. BATT information system was released in the middle of-2017 ago. This study aimed to understand the condition of quality and the successful of implementation of information system of Batu Teknologi Among Tani (BATT). This study was conducted with a combined model of Technology Acceptance Model (TAM) and Delone & Mclean. The data used were 160 respondents by using purposive sampling. The data were collected through questionnaires. The results of quality analysis on perceived usefulness, actual system use variable included to category of very high, and perceived ease of use variable, attitude towards using, behavioral intention to use included to category of high. The results of the successful analysis on the system quality variable, information quality variable, use, user satisfaction included to category of high, service quality included to category of high enough, and the net benefits variable included to category of very high. The results of the quality of BATT information system implementation based on the TAM model are in the high category with a percentage of 79.0% and the successful implementation based on the Delone & Mclean model is in the high category with a score of 77.37%.